Proposed business strategy for it industry company (case study of mii) - Nathaniel Hartono, Christian; Aditya Wibowo, Satya (The Indonesian Journal of Business Administration, 2016)
Abstract - IT industry has been changing dynamically. The necessity of the customer has been shift from buying assets to renting and outsourcing to 3rd party vendor. The needs to reduce capital expenses is one of the reason. Minimize the risk for IT project is the second reason. The rapid pace of technological change demand for IT division proactively identify potential substitute as well as identify newly emerging technologies in which firm could sustain competitive advantage. The business environment which are influencing the company performance are political and economic factor in Indonesia. Recent presidential election also play a major disadvantage for the growth of the company. IT industry regulator is mainly from MENKOMINFO in which put into effective several ITE regulations that also embrace every company to use licensed software and hardware. IT investment become expensive and demand for maintenance cost to be consider. 3rd party IT vendor should be able to capture the requirement and shift the business focus to service industry. Based on the analysis using fishbone diagram several root cause has been analyzed thoroughly. The unreliable delivery of Service Level Agreement, Lacks of excellence service to the customer, issue of human Resource inside the Managed Service Business Unit (MSBU) that causing high turnover, and field engineers lack of basic soft skills. Moreover no dedicated service and quality division is one of the reason why MII hardly improve the selling of managed service. Proposed solution is to create differentiation that will enhance MII sustainable value. According to strategy diamond model, firm should maintain its premium price with a distinct service quality. Implementation plan will be 6 month period. Established new Service and Quality division will be the starting point for the firm. Management review should be the controller for each implementation staging. Preventive action should be prepared in case there are resistance from couple of employees and also corrective action in order to redo the needed staging.Â Key Words: IT, root cause, corporate strategy, strategy diamond model, implementation plan